AB0521 Short Term Effect of Belimumab on Endothelial Progenitor Cells in Patients with Systemic Lupus Erythematosus. (9th June 2015) - Spinelli, F.R.; Barbati, C.; Massaro, L.; Ceccarelli, F.; Morello, F.; Miranda, F.; Truglia, S.; Orefice, V.; Alessandri, C.; Conti, F.; Valesini, G.
Abstract : Background: Circulating endothelial progenitor cells (EPCs) are bone marrow-derived cells able to differentiate into mature endothelial cells; impairment of number and function of these cells is associated with increased subclinical atherosclerosis. Cardiovascular risk is highly increased in patients with Systemic Lupus Erythematosus (SLE). Several studies demonstrated that EPCs are reduced and impaired in SLE patients, partially accounting for the endothelial dysfunction characterizing these patients. In murine models, the inhibition of B Lymphocyte Stimulator (BLyS) was associated to a reduction of atherosclerotic plaque. In vivo effect of Belimumab, a monoclonal antibody targeting BLyS, on atherosclerotic process has not been yet addressed. Objectives: Aim of the study was to assess the short-term effect of Belimumab treatment on EPC number in SLE patients. Methods: We enrolled consecutive patients with SLE diagnosed according to 1997 ACR criteria due to start Belimumab for unresponsiveness to standard therapy. Patients with known cardiovascular disease were excluded. As control, we studied age and sex-matched healthy subjects. SLE disease activity was evaluated by SLEDAI 2K at baseline and after 4 and 12 weeks of Belimumab treatment. Blood samples were collected at the same time-point in heparinized vials. Blood samples from healthy subjects were collected on the same day of baseline patients' visit. Peripheral blood mononuclear cells (PBMCs) were incubated with fluorescein isothiocyanate-labeled anti-CD34 monoclonal antibodies and phycoerythrin-labeled anti VEGF-R2/KDR; acquisition was performed by flow cytometry. EPCs were defined as CD34/KDR double-positive cells. Kolmogorov-Smirnov showed the normal distribution of EPCs; data were expressed as mean ± standard deviation. To test the hypothesis that Belimumab may increase EPCs number we used one-tailed T-test. A p value <0.05 was considered statistically significant. Results: We enrolled 7 female patients (age 45.6±11.2 yrs, disease duration 17.8±10.8 yrs) with active disease (mean baseline SLEDAI 8.4±2.6). After 4 and 12 weeks we observed a trend in disease activity reduction (p=ns). Baseline EPC mean number was significantly lower in SLE patients compared to healthy subjects (0.072 ± 0.004 vs 0, 025 + 0.02, p=0.01). At week 4, the mean number of EPC increased to 0.019 ± 0.02 (p=0.025 vs baseline; p=n.s. vs NHS); at week 12 we did not observe any difference compared to baseline nor week 4. We did not find a correlation between SLEDAI and EPCs number at any time-point. Conclusions: The results of our pilot study demonstrate, for the first time, the short-term effect of Belimumab on EPC number in SLE patients. Several studies in mouse models established a role for B cells in atherosclerosis. Anti-BLyS could act by selectively depleting B2 cells, a sub-population of B lymphocytes with pro-atherogenic properties or, indirectly, by modulating other pro-inflammatory cytokines as well as Th17 cells, involved in the atherosclerotic process. Disclosure of Interest: None declared